Uma estimação dos determinantes de demanda por cinema no Brasil: um estudo sobre o setor para o ano de 2011 - Collaço, Cláudia da Escóssia (2013)
The purpose of this study was to analyze the film industry in Brazil, qualitative and historically, through the devices of incentives promoted by Laws Audiovisual and Rouanet. From the microeconomic approach on the demand for cultural goods, we sought to estimate the demand for movies in Brazil, to identify individual characterisitcs that influence the preferences of the individual, considering their behavior, their choices, te average prices of tickets and income. Were analyzed using the methodology parameters estimation in which the variable to display total revenue is determined by socioeconomic and market. We analyzed all the municipalities that have film. using data from the Portal B Movie, ANCINE and IBGE, the model estimated in cross-section, for the year 2011, pointed out that expenditure on film is determined by income, popultaion and number of theaters. The variable of education, cultural level proxy of municipalities, was not significant in the model, contrary to expectations. We conclude that the demand movie follows the regional inequalities in the country. To have a better distribution and acces to cultural, public policy should be guided in supporting thoes who actually need the federal incentives.